Music-mechanisms at the core of music therapy: Towards a format for a description of music therapy micro-interventions. - Hakvoort, Laurien; Tönjes, Djemida (Nordic Journal of Music Therapy, 2023)
The quality and quantity of music therapy research are increasing, as are the number of systematic reviews and meta-analyses. However, the latter often define the effect of music therapy treatment as inconclusive. This is frequently due to a lack of clear description of the intervention or the core function of music. Clearly described music therapy interventions might lead to improved treatment fidelity. This article offers a possible solution in three parts. First, limitations in music therapy research are discussed. Second, the design for a format of a practice-based intervention description is explained. In the third part of the article, an example illustrates the use of the format. The suggested micro-intervention format could lead to a greater reliability in empirical research through the recognition of the working-mechanisms of music therapy intervention at a micro-level. The micro-intervention format was created in collaboration with practicing music therapists, Master students, and a board member for scientific innovation of a professional association. The micro-intervention format allows music therapists to describe music therapy interventions in detail, including the intervention and its musical working-mechanisms. The format is intended to guide music therapists to execute their intervention in comparable manners, which in the case of a scientific study could improve research fidelity. "Music therapeutic guidance to reduce agitation in dementia care using improvisation and familiar songs" is used to illustrate the micro-intervention format. Development and dissemination of music therapy micro-interventions could lead to improved research outcomes and strengthen the evidence-based foundation of the profession.